Design and implementation of a programmable logic controller using PIC18F4580 - Sanver, Ufuk; Yavuz, Erdem; Eyupoglu, Can; Uzun, Tuncay (2018 IEEE Conference of Russian Young Researchers in Electrical and Electronic Engineering (EIConRus), 2018)
Use of electricity in industry opened a new age which is dominated by industrial automation. In the beginning, automation systems were based on electro-mechanical systems consisting of relays and contactors. Developments in semiconductor technology inevitably transformed the existing structure and cause electronic-controlled Programmable Logic Controller (PLC) to prevail in the automation systems. PLCs consist of a microcontroller/microprocessor, relay or transistor for switching, isolating equipment such as opto-couplers and voltage converter/inverters. Industrial PLCs are quite expensive devices. In this study, design and implementation of a low-cost PLC using PIC18F4580 microcontroller are realized. Special software including a graphical user-interface is developed for programming the PLC and transferring code data to the device. Both ladder diagram and word instructions can be used for programming the PLC.